Leveraging nanocrystal HKUST-1 in mixed-matrix membranes for ethylene/ethane separation - Chuah, Chong Yang (2021)
The energy-intensive ethylene/ethane separation process is a key challenge to the petrochemical industry. HKUST-1, a metal-organic framework (MOF) which possesses high accessible surface area and porosity, is utilized in mixed-matrix membrane fabrication to investigate its potential for improving the performance for C₂H₄/C₂H₆ separation. Prior to membrane fabrication and gas permeation analysis, nanocrystal HKUST-1 was first synthesized. This step is critical in order to ensure that defect-free mixed-matrix membranes can be formed. Then, polyimide-based polymers, ODPA-TMPDA and 6FDA-TMPDA, were chosen as the matrices. Our findings revealed that 20 wt% loading of HKUST-1 was capable of improving C₂H₄ permeability (155% for ODPA-TMPDA and 69% for 6FDA-TMPDA) without excessively sacrificing the C₂H₄/C₂H₆ selectivity. The C₂H₄ and C₂H₆ diffusivity, as well as solubility, were also improved substantially as compared to the pure polymeric membranes. Overall, our results edge near the upper bound, confirming the effectiveness of leveraging nanocrystal HKUST-1 filler for performance enhancements in mixed-matrix membranes for C₂H₄/C₂H₆ separation.